The Role of Pregnancy Concerns in the Relationship between Substance Use and Unprotected Sex among Adolescents. (7th June 2019) - Dir, Allyson L.; Hulvershorn, Leslie A.; Aalsma, Matthew C.
Abstract: Background : Substance use and unprotected sex are prevalent among adolescents. The link between substance use and unprotected sex is well-established. Research has also highlighted how adolescents' attitudes and risk perceptions regarding unprotected sex, including concerns about pregnancy ("Getting pregnant would force me to grow up too fast"), are associated with unprotected sex and unplanned pregnancy. However, less research has examined the potential relationship between pregnancy concerns and substance use among adolescents. Objectives : The study prospectively examined (1) differences in pregnancy concerns across patterns of substance use and (2) whether pregnancy concerns mediate the relationship between substance use and later unprotected sex among a sample of middle and high school students. Method: 98 adolescents [ M ( SD ) age = 14.28(1.68), 59.4% female, 59.4% black/African American] completed self-report measures of marijuana and alcohol use, pregnancy concerns, and unprotected sex across three time points over 6 months (T1–T3). Results: Substance users (alcohol/marijuana) reported fewer pregnancy concerns compared to non-substance users ( t  = 2.99, p = .04). Pregnancy concerns at T2 mediated the relationship between T1 lifetime substance use and later unprotected sex (T3) (indirect effect: b  = 0.10, CI [.01–.41]; direct effect: b  = 0.15, p = .32), controlling for gender, age, and race. More frequent substance use (T1) was related to fewer pregnancy concerns at T2 ( b = −0.10, p = .04); fewer pregnancy concerns were related to increased likelihood of later unprotected sex ( b = −1.02, p = .02). Conclusions: Findings offer new insight into associations between substance use and unprotected sex and suggest that substance use and sexual health interventions should target pregnancy concerns.